Implementasi Pendidikan Karakter Terhadap Perilaku Akademik Siswa Kelas VIII SMP Abdurahman Karangpawitan Garut - Raito, Raito; Maulana, Ahmad Yusuf (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
Self-awareness is crucial in the learning process, yet it remains a challenge among students. This is evident from students' inability to recognize their feelings and behaviors, identify their strengths and weaknesses, develop independence, make appropriate decisions, and effectively express their thoughts, feelings, opinions, and beliefs, which leads to low motivation for improving their learning processes. Therefore, the implementation of character education is an appropriate solution to address these issues. This study aims to describe the implementation of character education and its impact on the academic behavior of eighth-grade students at SMP Abdurahman Karangpawitan Garut. Based on the analysis conducted, the findings are as follows: (1) The implementation of character education among the eighth-grade students at SMP Abdurahman Karangpawitan Garut is satisfactory, as evidenced by 11 out of 20 respondents (55%) rating it as moderate. (2) The academic behavior of these students is also satisfactory, with all 20 respondents (100%) rating it as moderate. (3) There is a significant influence of character education implementation on the academic behavior of eighth-grade students, demonstrated by a t-value greater than the critical t-value, both at the 5% significance level (2.101) and the 1% significance level (2.878). The calculated t-value is 5.582 with N=20 at a significance level of 0.05 (5%) of 2.101 and at a significance level of 0.01 (1%) of 2.878, indicating that t-value > critical t-value or 5.582 > 2.101 > 2.878, thus rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha).  Keywords: Implementation of Character Education, Academic Behavior of Students